2014
DOI: 10.1007/s10195-014-0294-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade periprosthetic knee infection: diagnosis and management

Abstract: Diagnosis and management of low-grade periprosthetic knee infection are still controversial and debatable. The diagnosis of low-grade infection after total knee arthroplasty is often complex, as clinical symptomatology and diagnostic studies are highly conflicting and knees often exhibit well-fixed components. Although the criterion standard for staged reimplantation is interim placement of an antibiotic-loaded spacer, less-invasive surgical procedures have been advocated for managing infections caused by low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
2
21
0
2
Order By: Relevance
“…In implant infections lasting for more than 4 weeks, biofilm formation is complete and a PPI has developed [5]. In these cases, removal of the contaminated implant, extensive bone, and tissue debridement as well as prolonged antimicrobial treatment is recommended, demonstrating success rates for eradication between 81.0 and 94.6% [2,[5][6][7]. Our data show that sphingosine not only proved to be effective in preventing Replacing the sphingosine solution after 30 min even resulted in a complete eradication of sessile biofilm-grown S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In implant infections lasting for more than 4 weeks, biofilm formation is complete and a PPI has developed [5]. In these cases, removal of the contaminated implant, extensive bone, and tissue debridement as well as prolonged antimicrobial treatment is recommended, demonstrating success rates for eradication between 81.0 and 94.6% [2,[5][6][7]. Our data show that sphingosine not only proved to be effective in preventing Replacing the sphingosine solution after 30 min even resulted in a complete eradication of sessile biofilm-grown S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, radical debridement for PPI compromises function of the affected limb. Currently, single and two stage surgical treatment strategies in PPI have been developed demonstrating success rates for eradication between 81.0 and 94.6 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in cases of an assumed low-grade infection a remaining diagnostic uncertainty is possible [18]. In the present study we estimated serum inflammatory markers in every case, performed a diagnostic aspiration in six and a diagnostic arthroscopy in one case.…”
Section: Discussionmentioning
confidence: 93%
“…The latest studies were performed by Tibrewal et al [ 22 ] and Haddad et al [ 23 ] with re-infection rates of 2% and 0%, respectively. Other smaller retrospective studies till date have shown rates of between 0%-10% [ 15 , 20 , 22 - 24 ].…”
Section: Resultsmentioning
confidence: 99%